Research on space information representation model based on formal concept analysis - Shao-bo YU; Ling-da WU; Xi-tao ZHANG (Tongxin xuebao)
By discussing the concept,connotation and development situation of SI and its representation,and combining the content of FCA,the SIR model was established from there aspects including SI formal context,SI concept lattice and SI implication relation.Taking part of space entity sets and space data sets as input,the specific application of representation model on SIN was realized based on concept explorer platform,meanwhile,the effectiveness and feasibility of the SIR model was also validated by this example.Of course,the aim of the model was to provide information representation support for the basic theory and key technical research of SIN.